从“我”和“吾”的分布看《左传》中特殊的双宾结构 = A non-canonical double-object construction in Zuozhuan based on the distribution of two first person pronouns - 张嘉慧 Chong, Ka Wuei (2009)
“我”和“吾”是上古汉语中常用的第一人称代词，现有的研究多从语法的角度着眼探究，指出第一人称代词特有的语法位置，大体皆认为“我”和“吾”之间的语法功能是有区别的、互相分工的。在《左传》里，我们观察到“V 军+我+NP 处”这类句式，例如“伐我北鄙”，传统一般倾向于作单宾结构的解释。观察所得，出现在“V 军”位置上的动词皆是与军事活动有关的动词；而“NP 处”位置上出现的可以是处所名词或者地方名词，唯独在第一人称代词“我”的位置上是不能被“吾”所取代的。 “我”和“吾”都能作定语，从理论上而言，两者之间应该可以相互替换，然而，在《左传》中的“V 军+我+NP 处” 句式却没有“我”和“吾”的交替现象，形成了不对称的分布。本文倾向于将“V 军+我+NP 处”作双宾结构解，“V 军”以二价动词进入双宾结构，并不符合一般的双宾结构。因此，文中将逐步说明“V 军+我+NP 处”分析为单宾结构所面对的难处，主要从语法、语用和语义的角度进行剖析，最后，通过与给予类双宾结构的平行现象来证明“V 军+我+NP 处”句式可解为双宾结构，最后通过语义地图的推导，证明“V 军+我+NP 处”句式具有解为双宾结构的可能性。 The first person pronoun wǒ我 and wú吾 is commonly used in Archaic Chinese. Most of the linguists believe that there is a specific grammatical position and a distinction of grammatical function between wǒ我 and wú吾. Based on existing research, phrases such as fa wo bei bi 伐我北鄙 ‘invaded our northern borders’ (generalized as “V军+ wǒ我 +NP处” later in an article) is found in Zuozhuan. Majority of the linguists are inclined towards the view that the construction fa wo bei bi 伐我北鄙 ‘invaded our northern borders’ should be regarded as a simple object construction. Based on our research, in the construction “V军+ wǒ我 +NP处”, the verb V军 is related to military affairs while NP处 is either noun of location or noun of place. The first person pronoun wǒ我in the construction cannot be replaced by wú吾. According to grammatical theory, both wǒ我 and wú吾 can be used as a modifier. Thus, there should be an alternation between them. On the contrary, there are contrast and asymmetry of the construction “V军+ wǒ我 +NP处”.This paper insists that the construction “V军+ wǒ我 +NP处” should be analyzed as double-object construction. A typical double-object construction will always include three NPs as their arguments. However, the construction “V军+ wǒ我 +NP处” does not meet this criterion as the verbs are inherently two-valence instead of three-valence. This will lead to doubts on how it can be possible for the inherently two-valence verbs to form a double-object construction? How can “V军+ wǒ我 +NP处” be regarded as a double-object construction? This paper provides a thorough analysis and view from the angle of grammatical, pragmatic and semantics approaches. This research strongly supports the claim that “V军+ wǒ我 +NP处” should be regarded as a double-object construction which is further supported by the data. This paper explores a point which has drawn special attention from the scholars, which is to explore a special type of double-object construction in Zuozhuan. This paper, with ample explanation, demonstrates that double-object analysis is better choice to the construction “V军+ wǒ我 +NP处”.